Financial literacy and its development prospects: insights from Hungarian and international literature - Zentai, Péter; Molnárné Kovács, Judit (Public Finance Quarterly, 2024)
To attain financial well-being, enhancing financial literacy is crucial; however, the definition of financial literacy is inconsistent both in Hungarian and international literature. In Hungary, the distinction between individual and the societal levels is not clear either. Accordingly, we conducted a literature review, during which our method involved collecting meta-studies in English containing the term “financial literacy” and selectively reviewing the research presented in them based on relevance. In Hungarian, we examined which terms have become common equivalents for “financial literacy” and analysed the related literature along these lines. In the theoretical model created in our study, we conceptualize financial literacy in a new way, and to capture the individual level, we recommend the introduction of a new Hungarian term. With regards to Hungarian results, high knowledge is combined with low levels of financial behaviour, so we recommend that decision-makers use behavioural economic tools instead of traditional financial education, which have a more direct impact on people’s everyday financial behaviour and operate more widely in those layers of society where traditional financial education have proven to be ineffective.